2000
DOI: 10.1143/jpsj.69.3878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Correlation between Molecular Diffraction and Rotational Excitation on the Scattering Dynamics of H2from Cu(001)

Abstract: We perform quantum dynamics calculations that include all six degrees of freedom of a H 2 and investigate the effects of the correlation between the molecular diffraction and rotational excitation on the dynamics of H 2 scattered from Cu(001). Our calculation results show that when the H 2 undergoes diffraction on Cu(001) and assumes helicopter-like rotation, the rotationally inelastic diffraction (RID) probability (with the rotational quantum number j changing from j = 0 → 2, and the corresponding azimuthal q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The similarity between tunneling and scattering problems also allows for further applications in molecular physics. The scattering of H 2 from Cu (001) [21] and NO from diamond (110) [22] have been shown to produce energy resonances similar to those predicted in earlier works utilizing time-independent formulations.…”
Section: Future Worksupporting
confidence: 67%
See 1 more Smart Citation
“…The similarity between tunneling and scattering problems also allows for further applications in molecular physics. The scattering of H 2 from Cu (001) [21] and NO from diamond (110) [22] have been shown to produce energy resonances similar to those predicted in earlier works utilizing time-independent formulations.…”
Section: Future Worksupporting
confidence: 67%
“…The limits of integration for P Sν (t) correspond to the range of the effective potential inx (for L/a = 10, the effective potential vanishes for |x| > 5). From (20), (21), and (22), we may define the probabilities of reflection, transmission, and straddling in the bound state and in an unbound state as follows:…”
Section: Results Of the Numerical Analysismentioning
confidence: 99%
“…Experimental work on threedimensional molecular scattering is a current area of research. Recent work includes the scattering of Hg from Cu(OOl) [36] and NO from Diamond(llO) [37]. In these works it is shown that some energies are scattered more than others,…”
Section: Extension To More Realistic Systemsmentioning
confidence: 99%
“…We report isotope effects on hydrogen abstraction from Cu(111) for a surface coverage H = 0.500 monolayers (ML), which corresponds to 1.08 × 10 14 atoms cm −2 . We perform quantum dynamics calculations which quantum mechanically include both the direct and indirect processes by using the numerically stable time-independent coupled-channel method [23,25].…”
Section: Introductionmentioning
confidence: 99%